PENGGUNAAN MEDIA PUZZLE HURUF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA PADA KELAS 1 SDN SUMBEREJO 03 KOTA BATU - Tria Melati Agustina; Mohammad Afifulloh; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Reading is one of the foundations for students to understand a learning material, besides reading is a tool to communicate, and a tool to understand the material. Beginning reading starts from an early age or in low grades such as grade I and grade II, which requires special attention and strategies when learning either method or media. Due to low grade students in the learning process students often feel bored, so the teacher is more effective by using a media or method that is suitable for the learning. One of the learning media that can be used to read beginners is the letter puzzle media. Reading with the Puzle Letter media in the learning process will be more fun and the learning atmosphere will be more lively.